Diagnosis and management of malignant peripheral nerve sheath tumors: Current practice and future perspectives. (14th November 2019) - Prudner, Bethany C; Ball, Tyler; Rathore, Richa; Hirbe, Angela C
Abstract: One of the most common malignancies affecting adults with the neurofibromatosis type 1 (NF1) cancer predisposition syndrome is the malignant peripheral nerve sheath tumor (MPNST), a highly aggressive sarcoma that typically develops from benign plexiform neurofibromas. Approximately 8–13% of individuals with NF1 will develop MPNST during young adulthood. There are few therapeutic options, and the vast majority of people with these cancers will die within 5 years of diagnosis. Despite efforts to understand the pathogenesis of these aggressive tumors, the overall prognosis remains dismal. This manuscript will review the current understanding of the cellular and molecular progression of MPNST, diagnostic workup of patients with these tumors, current treatment paradigms, and investigational treatment options. Additionally, we highlight novel areas of preclinical research, which may lead to future clinical trials. In summary, MPNST remains a diagnostic and therapeutic challenge, and future work is needed to develop novel and rational combinational therapy for these tumors.